Ghrelin Inhibits Intestinal Epithelial Cell Apoptosis Through the Unfolded Protein Response Pathway in Ulcerative Colitis - Zhang, Lin; Cheng, Jian; Shen, Jie; Wang, Sheng; Guo, Chuanyong; Fan, Xiaoming (Frontiers in Pharmacology, 2021)
Ulcerative colitis (UC) is a type of inflammatory bowel disease (IBD) which occurs in the lining of the rectum and colon. Apoptosis of the intestinal epithelial cells (IECs) is common in active UC patients. Ghrelin is reported to be downregulated in tumor necrosis factor (TNF)-α-induced apoptosis of IECs. Therefore, we hypnotized that ghrelin might play the anti-apoptotic role in UC progression and investigated it through in vitro and in vivo studies. TNF-α-treated Caco-2 cell model and mouse colitis model induced by dextran sulfate sodium (DSS) or 2,4,6-Trinitrobenzenesulfonic acid (TNBS) were established and employed. We found that ghrelin could inhibit the apoptosis of Caco-2 cells induced by TNF-α, which could be disturbed by [D-lys3]-GHRP-6, the antagonist of ghrelin receptor GHS-R1a. Similarly, in DSS- and TNBS- induced mouse colitis model, ghrelin also could protect intestinal tissues from apoptosis in DSS- and TNBS- induced colitis depending on GHS-R1a. Furthermore, ghrelin modulated unfolded protein response (UPR) pathway, and regulated the expression of caspase-3, BAX and Bcl-2, which contributed to the inhibition of cell apoptosis. In conclusion, ghrelin protects IECs from apoptosis during the pathogenesis of colitis through regulating UPR pathway.